Natural Phytotherapeutic Antioxidants in the Treatment of Mercury Intoxication-A Review - Velid Unsal (Tabriz University of Medical Sciences, 2018)
Heavy metals taken into the organism can make the toxic effects on the metabolism in various ways. For example, they may interact with proteins to alter and inhibit their enzymatic and structural functions. Mercury is one of the toxic elements that are widely distributed in nature. Mercury toxicity poses a serious threat to human health. It is an element that causes oxidative stress to increase in individuals, leading to tissue damage. Oxidative stress is the result of the imbalance between the production of oxidative species and cellular antioxidant defense. Phytotherapy continues to play an important role in health care. Natural phytotherapeutic antioxidants, exhibit a broad sequence of biological impacts, including anti-oxidative stress, anti-aging, anti-toxicicity and anticancer. Many studies have also shown that the phytotherapeutic agents play an important role in the removal of mercury from the tissue and in reducing oxidative stress. Our goal in this review was to investigate alternative ways of extracting the mercury in the tissue.